ACADEMIC ANXIETY SISWA SEKOLAH DASAR DI ERA DIGITAL: ANALISIS BERDASARKAN FAKTOR DEMOGRAFIS DAN POLA ASUH - Fatia Mumtaz; Siti Sarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the level of academic anxiety of elementary school students in the digital era based on demographic factors and parenting patterns, with a focus on differences in gender, school origin, grade level, and parenting patterns. The approach used is descriptive quantitative with a survey technique. The subjects of the study were students in grades IV-VI from two elementary schools in Majalengka Village representing public schools and Islamic schools. Data were collected through a Likert scale questionnaire that has been tested for validity and reliability of 0.644. Data analysis used descriptive percentage techniques. The results showed that the level of academic anxiety was generally in the moderate to high category. Female students showed slightly higher levels of anxiety than male students. In addition, students in Islamic Elementary Schools (MI) had higher levels of academic anxiety compared to elementary school students. Meanwhile, sixth-grade students tended to have higher academic anxiety than fourth and fifth-grade students. Based on parenting patterns, students raised by both parents had higher academic anxiety than students from single parents or those raised by foster parents. The results of this study revealed that elementary school students' levels of academic anxiety vary based on their demographic characteristics and parenting styles. These findings underscore the importance of educational approaches that are responsive to students' psychosocial aspects in order to create a more supportive and emotionally healthy learning environment.